New Insights on Phytochemical Features and Biological Properties of Alnus glutinosa Stem Bark - Antonella Smeriglio; Valeria D’Angelo; Anna Cacciola; Mariarosaria Ingegneri; Francesco Maria Raimondo; Domenico Trombetta; Maria Paola Germanò (Plants, 2022)
Alnus glutinosa (namely black alder or European alder) is a tree of the Betulaceae family widely spread through Europe, Southeastern Asia, the Caucasus mountains, and Western Siberia. Its bark is traditionally used for medicinal purposes as an astringent, cathartic, febrifuge, emetic, hemostatic, and tonic, suggesting that it may contain bioactive compounds useful to counteract inflammation. The aim of this study was to investigate the phytochemical profile of A. glutinosa stem bark extract (AGE) by LC-DAD-ESI-MS/MS analysis and to validate some biological activities such as antioxidant, anti-inflammatory and anti-angiogenic properties by in vitro and in vivo models (chick chorioallantoic membranes and zebrafish embryos), that can justify its use against inflammatory-based diseases. The AGE showed a high total phenols content expressed as gallic acid equivalents (0.71 g GAE/g of AGE). Diarylheptanoids have been identified as the predominant compounds (0.65 g/g of AGE) with oregonin, which alone constitutes 74.67% of the AGE. The AGE showed a strong and concentration-dependent antioxidant (IC50 0.15–12.21 µg/mL) and anti-inflammatory (IC50 5.47–12.97 µg/mL) activity. Furthermore, it showed promising anti-angiogenic activity, inhibiting both the vessel growth (IC50 23.39 µg/egg) and the release of an endogenous phosphatase alkaline enzyme (IC50 44.24 µg/embryo). In conclusion, AGE is a promising source of antioxidant, anti-inflammatory and angio-modulator compounds.